Southern Italian teenagers: the older they get, the unfit they become with girls worse than boys. Issue 51 (December 2017) - Jemni, Monèm; Zaman, M. Justin; La Rocca, Daniela; Tabacchi, Garden
Abstract : Abstract: Italy comprises a high proportion of people who never exercised. Low physical activity levels in adolescents is a risk factor for several disorders. The aim of this cohort epidemiological study was to compare physical fitness profiles between boys and girls with regard to age and gender and to identify health and fitness-related markers that contribute to the make-up of Southern Italian teenagers. Eight hundred eleven teenagers were assessed for anthropometric measurements and completed the 5 ASSO-fitness tests battery. Data were analyzed with a 2-way analysis of variance (ANOVA) for repeated measures to compare the effect of both age and gender on the fitness components. The boys' anthropometric measurements were superior than the girls as expected [weight, height, body mass index (BMI), and waist circumference]; the overall BMI was found in the normality range. The overall teenagers' fitness markers were found to be quite poor with the boys outperforming the girls in all fitness tests. The weak cardiorespiratory performance of the female teenagers was remarkable. The under 16 years old (-16 yrs) girls outperformed the over 16 years old (+16yrs) girls. There were less significant differences when comparing (-16) and (+16) yrs old mixed-gender groups. There were no correlations between the (−16) and (+16) yrs when both genders were considered. The trend analysis showed the younger teenagers might be "catching up" the older ones in both contexts. Gender significantly influenced all variables. Although age did not influence cardiorespiratory fitness, the older the teenagers the worse their health and fitness markers become with the older girls worse than their younger peers.